Relationship between economic insecurity, inflammation, monocyte activation and intestinal integrity in children living with HIV in Uganda. Issue 11 (1st November 2020) - Dirajlal-Fargo, Sahera; Albar, Zainab; Sattar, Abdus; Kulkarni, Manjusha; Bowman, Emily; Funderburg, Nicholas; Nazzinda, Rashidah; Kityo, Cissy; Musiime, Victor; McComsey, Grace A.
ABSTRACT: We aimed to evaluate differences in socio-economic variables in a Ugandan cohort of children with perinatally acquired HIV (PHIVs), HIV exposed uninfected (HEU) and HIV unexposed uninfected (HIV-) children and their associations with markers of inflammation and intestinal integrity. This is a cross-sectional study in 57 PHIV, 59 HEU and 56 HIV – children aged 2–10 years old enrolled in Uganda. Mean age of all participants was 7 years and 55% were girls. Compared to HEU and HIV – children, PHIVs were more likely to have parents that only completed a primary education, live in a household without electricity and live in poverty ( p ≤0.034). PHIVs living in poverty had higher IL-6 ( p =0.006), those with lack of electricity had higher hsCRP, IL6, sTNFRII and d-dimer ( p ≤0.048) and PHIVs with an unprotected water source had higher IL6 and d-dimer ( p ≤0.016). After adjusting for demographic and HIV variables, IL-6 and d-dimer remained associated with lack of electricity and having an unprotected water source only in PHIVs ( p <0.019). Our findings suggest that addressing economic insecurity may mitigate the persistent low-level inflammation in HIV that lead to many end organ disease. Longitudinal studies are needed to better understand the impact of socioeconomic factors on HIV inflammation and comorbidities.